Integrating BIM and AI for Smart Construction Management: Current Status and Future Directions - Pan, Yue; Zhang, Limao (Archives of computational methods in engineering, 2023)
At present, building information modeling (BIM) has been developed into a digital backbone of the architecture, engineering, and construction industry. Also, recent decades have witnessed the fast development of various AI techniques in reliably tackling a huge amount of data under complex and uncertain environments. Since both BIM and artificial intelligence (AI) have attracted sustainable attention, the integration of BIM and AI can demonstrate newly added value in handling construction projects with inherent complexity and uncertainty. For a clear understanding of BIM-AI integration in boosting smart construction management, the goal of this paper is to make a comprehensive investigation and summary of its potential value and practical utility to drive the construction industry to catch up with the fast pace of automation and digitalization. Through both the bibliometric analysis and information analysis, this paper provides a deep insight into the status quo and future trends for leveraging AI during the entire lifecycle of a BIM-enabled project. It is worth noting that keywords that are highly cited in the latest two years contain deep learning, internet of things, digital twin, and others, which means AI is evolving as the next frontier to accelerate the revolution in the traditional civil engineering. According to keyword clusters derived from the log-likelihood ratio, we determine six advanced research interests and discuss the state-of-the-art research, including automated design and rule checking, 3D as-built reconstruction, event log mining, building performance analysis, virtual and augmented reality, and digital twin. Besides, a growing force can be put on three potential directions to more broadly adopt the BIM-AI integration, including synthesis of human–machine intelligence, civil-level digital twin, and blockchain, aiming to make BIM and AI live up to expectations.